Evaluation of an experimental rat model for comparative studies of bleaching agents - Cintra, Luciano Tavares Angelo [UNESP]; Benetti, Francine [UNESP]; Ferreira, Luciana Lousada [UNESP]; Rahal, Vanessa [UNESP]; Ervolino, Edilson [UNESP]; Jacinto, Rogério de Castilho [UNESP]; Gomes Filho, João Eduardo [UNESP]; Briso, André Luiz Fraga [UNESP] (Univ Sao Paulo Fac Odontologia Bauru, 2016)
Dental materials, in general, are tested in different animal models prior to their clinical use in humans, except for bleaching agents. Objectives: To evaluate an experimental rat model for comparative studies of bleaching agents by investigating the influence of different concentrations and application times of H2O2 gel in the pulp tissue during in-office bleaching of rats' vital teeth. Material and methods: The right and left maxillary molars of 50 Wistar rats were bleached with 20% and 35% H(2)O(2)gels, respectively, for 5, 10, 15, 30, or 45 min (n=10 rats/group). Ten animals (control) were untreated. The rats were killed after 2 or 30 days, and the maxillae were examined by light microscopy. Inflammation was evaluated by histonnorphonnetric analysis with inflammatory cell counting in the corona| and radicular thirds of the pulp. The counting of fibroblasts was also performed. Scores were attributed to the odontoblastic layer and to vascular changes. The tertiary dentin area and the pulp chamber central area were histonnorphometrically measured. Data were compared by the analysis of variance and the Kruskal-Wallis test (p<0.05). Results: After 2 days, the amount of inflammatory cells increased in the occlusal third of the corona| pulp until the time of 15 min for both concentrations of bleaching gels. In 30 and 45 min groups of each concentration, the number of inflammatory cells decreased along with the appearance of necrotic areas. After 30 days, a reduction in the pulp chamber central area and an enlargement of tertiary dentin area were observed without the detection of inflammation areas. Conclusion: The rat model of extra coronal bleaching showed to be adequate for bleaching protocols studies, as it was possible to observe alterations in the pulp tissues and in the tooth structure caused by different concentrations and periods of application of bleaching agents.
Keywords: Bleaching agents; Animal models; Hydrogen peroxide